2009
DOI: 10.1038/hr.2009.22
|View full text |Cite
|
Sign up to set email alerts
|

Association of candidate gene polymorphisms with chronic kidney disease in Japanese individuals with hypertension

Abstract: Although hypertension has been recognized as a risk factor for chronic kidney disease (CKD), the genetic factors for predisposition to CKD in individuals with hypertension remain largely unknown. The purpose of this study was to identify the genetic variants that confer susceptibility to CKD among individuals with hypertension. The study population comprised 3696 Japanese individuals with hypertension (2265 men, 1431 women), including 1257 individuals (789 men, 468 women) with CKD (estimated glomerular filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Data regarding linkage with regions identified in this study on chromosomes 2, 3, 4, 10, 13, 16 and 20 were supported by smaller linkage studies or studies of chromosomal rearrangements associated with vur, usually in association with other urinary tract malformations. 22,[127][128][129][130][131][132][133] For example, the second highest linkage peak in this study was in chromo some 10q26, with the linkage peak clearly distal to potential candidate genes FGFR2 and PAX2. a study of 10 patients with monosomy of 10q26 and urinary anomalies (such as vur and hypoplastic kidney) with or without genital anomalies provided evidence for a gene or genes involved in kidney development in the same region.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 58%
See 2 more Smart Citations
“…Data regarding linkage with regions identified in this study on chromosomes 2, 3, 4, 10, 13, 16 and 20 were supported by smaller linkage studies or studies of chromosomal rearrangements associated with vur, usually in association with other urinary tract malformations. 22,[127][128][129][130][131][132][133] For example, the second highest linkage peak in this study was in chromo some 10q26, with the linkage peak clearly distal to potential candidate genes FGFR2 and PAX2. a study of 10 patients with monosomy of 10q26 and urinary anomalies (such as vur and hypoplastic kidney) with or without genital anomalies provided evidence for a gene or genes involved in kidney development in the same region.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 58%
“…the esrD study also revealed evidence for linkage at 10q26, 1q25, 6q24 and 4p15.32, 130 all of which are close to or overlapping with regions identified by Kelly et al the CKD candidate gene study provided support for loci identified by Kelly et al at 6q24-q25, 16q24.3, and 20p11.2. 133 these results indicate that the study of the genetics of vur has wider implications than the understanding of vur alone, and is likely to be important to the understanding of chronic renal disease and renal failure.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 93%
See 1 more Smart Citation
“…a total of 150 polymorphisms (data not shown) were selected by genome-wide association studies of ischemic stroke and myocardial infarction (p-value for allele frequency <1.0x10 -7 ) with the use of the Genechip human mapping 500K array Set (affymetrix, Santa clara, ca, uSa) (14). the relationship of these polymorphisms to cKd was not previously examined in our studies (9)(10)(11)(12)15,16).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, given ethnic differences in lifestyle and environmental factors as well as in genetic background and renal function, it is necessary to examine genetic variants related to cKd in each ethnic group. We previously showed that genetic variants that confer susceptibility to cKd differ between individuals with or without metabolic syndrome (9), with or without type 2 diabetes mellitus (10), with or without hypertension (11), or with different lipid profiles (12). To further examine whether the association of polymorphisms with CKD is influenced by the absence or presence of hypertension or diabetes mellitus, we performed an association study for 150 polymorphisms of…”
Section: Introductionmentioning
confidence: 99%